DIRECTIONS FOR DIGITAL IMAGE PROCESSING: DIRECTIONS FOR DIGITAL IMAGE PROCESSING - Peneva, Velichka; Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Applications of digital imaging include a wide variety of fields, and advances in image processing allow for the generation of three-dimensional reconstructions, object detection, and analysis, providing new possibilities for image visualization and recognition.